Donations to Political Parties: Investing Corporations and Consuming Individuals?. (May 2017) - Fink, Alexander
Summary: What motivates donations to political parties? Two views prevail. Donors are perceived either as ideologically motivated consumers or as privilege‐seeking investors. To investigate differences in donor motivation between corporations and individuals, we analyze data from Germany. For the period from 1994 to 2014, we find that corporations act more like investors than individuals do. First, we test whether corporations or individuals are more inclined to give more to incumbent parties than to parties outside the governing coalition. Giving to incumbent parties whose representatives hold public offices may be more attractive for investing donors. Second, we test for differences between corporations and individuals in the relative increase in donations from non‐election years to election years. Investor donations may be more volatile than consumer donations. We find that only corporations donate more to incumbent parties and that corporations increase their party donations from non‐election years to election years more than individuals do. These differences in the behavior of corporate and individual donors provide some evidence for potentially undesirable exchanges between corporations as investors and parties. Further, the differences between individual and corporate donors tend to be more consistent for parties to the right on the political spectrum.